In Vivo Fluorescence-Based Endoscopic Detection of Colon Dysplasia in the Mouse Using a Novel Peptide Probe - Miller, Sharon J. (Public Library of Science, 2011)
Colorectal cancer (CRC) is a major cause of cancer-related deaths in much of the world. Most CRCs arise from pre-malignant (dysplastic) lesions, such as adenomatous polyps, and current endoscopic screening approaches with white light do not detect all dysplastic lesions. Thus, new strategies to identify such lesions, including non-polypoid lesions, are needed. We aim to identify and validate novel peptides that specifically target dysplastic colonic epithelium in vivo. We used phage display to identify a novel peptide that binds to dysplastic colonic mucosa in vivo in a genetically engineered mouse model of colo-rectal tumorigenesis, based on somatic Apc (adenomatous polyposis coli) gene inactivation. Binding was confirmed using confocal microscopy on biopsied adenomas and excised adenomas incubated with peptide ex vivo. Studies of mice where a mutant Kras allele was somatically activated in the colon to generate hyperplastic epithelium were also performed for comparison. Several rounds of in vivo T7 library biopanning isolated a peptide, QPIHPNNM. The fluorescent-labeled peptide bound to dysplastic lesions on endoscopic analysis. Quantitative assessment revealed the fluorescent-labeled peptide (target/background: 2.17±0.61) binds ∼2-fold greater to the colonic adenomas when compared to the control peptide (target/background: 1.14±0.15), p<0.01. The peptide did not bind to the non-dysplastic (hyperplastic) epithelium of the Kras mice. This work is first to image fluorescence-labeled peptide binding in vivo that is specific towards colonic dysplasia on wide-area surveillance. This finding highlights an innovative strategy for targeted detection to localize pre-malignant lesions that can be generalized to the epithelium of hollow organs.